Development process of hospital information system (HIS) - Zainudin, Siti Nor Haslinda; Wan Mohd Hawari, Wan Nurfaezah Shafiqah; Ahmad Radzi, Farah Nabiha; Sarju, Norasyikin; Khairil Mokhtar, Nur Athirah (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
Hospital Information System (HIS) is essentially a computer system that can manage all the information to allow health care providers to do their jobs effectively1. This system can manage a wide range of hospital administration and management processes for the multispeciality hospital. In order to develop the system, it is necessary to analyze the requirements thoroughly to make sure the system meets the user requirement. Currently, the Hospital Information System contains Registration, Outpatient, Inpatient, Appointment and Medical Report modules. These modules act as different roles and components that totally run and deploy on a separate process. In developing HIS, it’s important to ensure the system can work effectively and efficiently by conducting testing. This system applied to three types of users which are doctors, nurse and system administration.